Transit-oriented economic development: The impact of light rail on new business starts in the Phoenix, AZ Region, USA - Credit, Kevin (Urban studies (Edinburgh, Scotland), 2018)
This article examines the impact of Phoenix’s light rail system, which opened in 2008, on new firm formation in specific industries. Individual business data from 1990–2014 are used in a quasi-experimental adjusted-interrupted time series (AITS) regression to compare the impact of the transit system’s construction on new business starts in ‘treatment’ and ‘control’ areas before and after the opening of the line. Findings show that the transit adjacency is worth an 88% increase in knowledge sector new starts, a 40% increase in service sector new starts and a 28% increase in retail new starts at the time the system opened, when compared with automobile-accessible control areas. However, the light rail also appears to suffer from a ‘novelty factor’ – after the initial increase in new establishment activity in adjacent block groups, the effect diminishes at the rate of 8%, 6% and 7% per year, respectively. The results also provide insight into the spatial extent of light rail impacts to new business formation, with areas 1 mile from stations observing 21% fewer retail new business starts and 12% fewer knowledge sector new starts than areas within a quarter of a mile of stations. 本文考察了亚利桑那州凤凰城 2008 年开通的轻轨对特定产业新公司组建的影响。我们在准实 验性的调整-中断时间序列(AITS)回归中运用1990-2014年的各企业数据，比较了轻轨开通前后 轨道交通体系建设对“影响” 区和“参照” 区新企业创立的影响。研宄结果表明，在轻轨开通 时，与依赖汽车的参照区相比，临近轨道交通站使知识型行业的新创企业增加了 88% , 使服务 业新创企业增加了 40% , 使零售业新创企业增加了 28%。但是，轻轨看来也受“新奇因素”的 影响一一临近轨道交通站的区域组经历了最初的新创企业增长后，其效应随后分别以每年 8%、6% 和 7% 的速度递减。研宄结果也说明了轻轨影响新企业组建的空间范围一一距离轨道交通站 1 英里范围的区域与距离轨道交通站 1/4 英里范围的区域相比，零售业新增企业要少 21% , 知识型行业新增企业要少12%。